(untitled) (Medico Legal Update, 2021)
It would not be an exaggeration of words if it is said that children are the future of a nation. They are the representatives of the older generation in the upcoming world. They are filled with innocence and their innocence should be nurtured so as to make it persistent and to make the society free of corruption. Their level of curiosity is very high and if it is preserved and explored then every child may become a researchoriented scientist, doctor, engineer or likewise. The most prominent international instrument through which the child right has got recognition is the Convention on Rights of Child, 1989. India being a signatory to it is complying with the standards laid down in it.